Pengaruh Personal Interest dan Self Control terhadap Minat Investasi pada Mahasiswa Generasi Z di Bandung - Budi Rustandi Kartawinata; Candra Wijayangka (Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
The purpose of this study was to find the influence of personal interst and self-control on investment interest in generation z students in Bandung. The method used in this research is quantitative method with descriptive and causal research types. The population in this study were students of generation z in Bandung. The sampling technique used is a non-probability sampling method with sub-sampling purposive sampling technique with a total of 270 respondents. The data analysis technique used descriptive analysis techniques and multiple linear regression analysis with the help of SPSS ver 22 software. The results of the study concluded that from the results of the t test, personal interest and self control had a positive and significant effect on investment interest in z generation students in Bandung. Based on the results of the F test, personal interest and self control together have an influence on investment interest in generation z students in Bandung.